Green synthesized novel silver nanoparticles and their application as anticoagulant and thrombolytic agents: A perspective. Issue 1 (March 2020) - Azeez, M A; Durodola, F A; Lateef, A; Yekeen, T A; Adubi, A O; Oladipo, I C.; Adebayo, E A; Badmus, J A; Abawulem, A O
Abstract: Effective management of haemostatic disorders in patients is pertinent in order to prevent complications attributable to incidences of thrombosis in atherosclerotic arteries to the heart, brain, limbs, stagnant blood in veins and heart chambers. The use of existing chemical agents are not without a number of challenges, varying from potential for unknown long-term adverse effect through lack of antidote for most agents, balance between cost and efficacy among others. However, advent of biogenic silver nanoparticles with anticoagulant and thrombolytic potentials has opened up a window of opportunity to address most of the shortcomings of the chemical synthesized anticoagulants. This review examined green synthesized novel silver nanoparticles, their characterization and possible application as anticoagulant and thrombolytic agents in the evolving area of nanomedicine.